Diagnostic validity of a marker model of first trimester in pregnancy in prediction of birth weight - Vujović, Slavica; Šćepanović, Andjelka; Terzić, Milan; Djurović, Milena (Vojnosanitetski pregled, 2022)
Background/Aim. Nowadays, low birth weight is considered to be one of the main causes of cardiovascular diseases or metabolic syndrome occurring later in life. Many studies have shown a strong impact of abnormal birth weight onto the future development, however, due to its stronger influence onto the development, a special emphasis is placed on low birth weight as compared to higher one. There is still no high-percentage accuracy test that will clearly classify expectant women under the risk of giving birth to a child too low or too big for gestational age. The aim of this paper was to set up a model that may indicate future low or high birth weight. Methods. This study included 191 expectant women who were divided  into three groups,  based on the birth weight (group 1: ˂ 3,000 g; group 2: 3,000–4,000 g; group 3: ˃ 4,000 g). The values of biochemical (pregnancy associated plasma protein A – PAPP-A, free β human chorionic gonadotropin) and ultrasonographic markers (nuchal translucency) as well as their multiple of the median (MoM) were determined and compared among groups. Results. It was shown that the values of PAPP-A MoM were considerably lower in groups of expectant women that had a fetus with low body weight (p = 0.003, p = 0.001). Statistically significant correlation between PAPP-A MoM and the newborn’s weight (rs = 0.221, p = 0.001) was proven among the groups examined within this study. Conclusion. The usage of a combination of biochemical parameters, sonographic and demographic data in screening program increases the chances for early identification of fetuses that are under higher risk for growth restriction or increased growth. Also, the increase in the value of PAPP- A MoM causes the increase of fetus’ body weight.
Keywords: chorionic gonadotropin, beta subunit, human; diagnosis; fetal growth retardation; forecasting; pregnancy; pregnancy-associated plasma protein-a; pregnancy trimester, first; ultrasonography